2004
DOI: 10.1001/archotol.130.5.598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temporal and Spectral Alterations of Speech Feedback on Speech Production by Persons With Hearing Loss

Abstract: To evaluate the effects of delay and spectral alteration of speech feedback (SF) on the speaking rate and voice pitch in adult users of hearing aids (HAs) and cochlear implants (CIs). Methods: Repeated-measure, completely crossed, 2-factor design. Spectral alterations were implemented by replacing SF with noise that was filtered into 1-, 2-, or 4-frequency bands and speech-modulated in real time. Delays varied from 25 to 200 milliseconds. Subjects: Seven HA users with severe to profound hearing loss and 6 CI u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…14,17,[25][26][27] Other evidence for vocal pitch control in CI users is found in studies showing decreased F0 in the presence of delayed auditory feedback, a reflexive behavior seen in NH individuals. 29,30 However, in contrast to studies showing changes in voice with acute changes in hearing, other studies have found more heterogeneous results. Some adults did not reduce F0 or SPL, whereas others actually increased these parameters.…”
Section: Cochlear Implants and Voicementioning
confidence: 94%
See 3 more Smart Citations
“…14,17,[25][26][27] Other evidence for vocal pitch control in CI users is found in studies showing decreased F0 in the presence of delayed auditory feedback, a reflexive behavior seen in NH individuals. 29,30 However, in contrast to studies showing changes in voice with acute changes in hearing, other studies have found more heterogeneous results. Some adults did not reduce F0 or SPL, whereas others actually increased these parameters.…”
Section: Cochlear Implants and Voicementioning
confidence: 94%
“…Delays in auditory feedback, known to cause slower speech and speech errors in NH listeners, also result in slower speaking rates in CI recipients. 29…”
Section: Cochlear Implants and Speech Rate Or Durationmentioning
confidence: 99%
See 2 more Smart Citations